Specific Physiological and Anatomical Traits Associated With Polyploidy and Better Detoxification Processes Contribute to Improved Huanglongbing Tolerance of the Persian Lime Compared With the Mexican Lime - Sivager, Gary; Calvez, Leny; Bruyere, Saturnin; Boisne-Noc, Rosiane; Brat, Pierre; Gros, Olivier; Ollitrault, Patrick; Morillon, Raphaël (Frontiers in Plant Science, 2021)
Huanglongbing (HLB) is presently a major threat to the citrus industry. Because of this disease, millions of trees are currently dying worldwide. The putative causal agent is a motile bacteria belonging to Candidatus Liberibacter spp., which is transmitted by psyllids. The bacteria is responsible for the synthesis of callose at the phloem sieve plate, leading to the obstruction of the pores that provide connections between adjacent sieve elements, thus limiting the symplastic transport of the sugars and starches synthesized in leaves to the other plant organs. The Persian triploid lime (Citrus latifolia) is one of the most HLB-tolerant citrus varieties, but the determinants associated with the tolerance are still unknown. HLB-infected diploid Mexican lime (Citrus aurantiifolia) and Persian lime were investigated. The leaf petiole was analyzed using scanning electron microscopy (SEM) to observe callose deposition at the phloem sieve plate. Leaf starch contents and detoxification enzyme activities were investigated. In the field, Persian lime leaves present more limited symptoms due to HLB than the Mexican lime leaves do. Photosynthesis, stomatal conductance, and transpiration decreased compared with control plants, but values remained greater in the Persian than in the Mexican lime. Analysis of the petiole sieve plate in control petiole samples showed that pores were approximately 1.8-fold larger in the Persian than in the Mexican lime. SEM analyses of petiole samples of symptomatic leaves showed the important deposition of callose into pores of Mexican and Persian limes, whereas biochemical analyses revealed better detoxification in Persian limes than in Mexican limes. Moreover, SEM analyses of infected petiole samples of asymptomatic leaves showed much larger callose depositions into the Mexican lime pores than in the Persian lime pores, whereas biochemical traits revealed much better behavior in Persian limes than in Mexican limes. Our results reveal that polyploids present specific behaviors associated with important physiological and biochemical determinants that may explain the better tolerance of the Persian lime against HLB compared with the Mexican lime.